Moxibustion for Herpes Zoster and Postherpetic Neuralgia: A Meta-Analysis - Yuanen Huang; Jingping Wu; Hongbin Cheng; Yanling Liu (Complexity)
Background. Herpes zoster (HZ) is a disease that mainly causes severe segmental neuralgia and vesicles after infection with herpes zoster virus (VZV). At the same time, more than 9 to 34 percent of patients have postherpetic neuralgia (PHN) present with chronic pain for months or even years. Moxibustion has been used to treat herpes zoster and postherpetic neuralgia for many years; however, there has been no comprehensive study to evaluate the efficacy and safety of moxibustion in the treatment of herpes zoster and postherpetic neuralgia. More studies evaluated the combined effects of acupuncture and moxibustion. Therefore, the purpose of this systematic review is to evaluate their efficacy and safety, so as to provide an evidence-based basis for the clinical application of moxibustion in the treatment of HZ and PHN. Method. The literature search was conducted in nine Chinese and English databases, and randomized controlled trials were pooled from their inceptions to June 2020. The included literature was screened, and data were extracted. RevMan 5.3 software and Stata software were used for statistical analysis. The primary outcome was the total effect. The secondary outcomes include VAS, NRS, and time of analgesia. Outcomes. From a total of 1957 identified studies, 31 were included in analysis (N = 2334 cases). 31 RCTs contained the experimental sample of 1185 cases and the control sample of 1149 cases reported efficiency of different moxibustions in the treatment of herpes zoster, statistical heterogeneity inspection without heterogeneity. So, we used the fixed-effects model, merge effect quantity OR = 3.89 (95% CI: 2.88∼5.25), Z = 8.86, and it suggested sample merger analysis was statistically significant. Also, the moxibustion, compared to other methods in the treatment of herpes zoster and herpes zoster neuralgia efficiency, increased significantly. The VAS scales, WMD = 1.69 (95% CI: 1.17∼2.22), and the time of analgesia, WMD = 2.41 (95% CI: 3.26∼1.73), indicated that moxibustion surpassed others in the relief of pain. NRS was just reported in one study. It was not statistically significant. There was no significant difference in adverse effects OR = 0.61 (95% CI: 0.33∼1.13), Z = 1.56 (P = 0.12). Conclusion. Moxibustion has obvious advantages over other therapies in the treatment of HZ and PHN. However, due to the obvious publication bias, the interpretation of the results should be cautious, and more rigorous randomized controlled clinical studies should be included to further confirm the results in the future.